The burden of trauma in the life of a refugee - Salim, Samina (Frontiers in Public Health, 2024)
My research on stress and trauma which began in a laboratory setting working with pre-clinical models of stress, has led me on a path that I wasn't planning on treading. In pursuit of expanding my understanding of trauma and stress, I focused my attention on the local refugee communities in Houston, Texas, USA. This has opened a plethora of information to me which I knew very little about or shall I say-I was unprepared to process. While conducting research focused on examining the impact of the trauma of war, displacement, and resettlement on mental well-being of refugees, I heard remarkable stories of survival from Houston-based refugee families. While the data we collected is amazing and intriguing, it has also been critical in inspiring me to look beyond data collection. Working with the refugee population has allowed me to look at science through many lenses; that of a scientist, an educator, a woman, a mother, an activist, and a global citizen. No matter which lenses I use for examining a refugee life, the resilience of the human spirit emerges as the most obvious conclusion, not to mention the hypocrisy of global politics. I propose creation of teams of "scientists without borders" who may serve as scientific ambassadors of public health and work towards promotion of global peace.